The Use of Amthãl Communication and Tafsir in Da'wa as a Learning Method for Developing the Islamic Community In Lombok - Mukhid, Abd; Udin, Udin; Saladin, Bustami (Universitas Islam Negeri Mataram, 2023)
Abd. Mukhid1, Udin2, Bustami Saladin3 1Madura State Islamic Institute, 2Universitas Islam Negeri Mataram email: mukhid.mjk@iainmadura.ac.id; bustamisaladin@uinmataram.ac.id; hmsudin@uinmataram.ac.id Abstract: Muslim preachers (da’i) must possess the skill of delivering messages. Communication, dialogue, speaking, listening, and understanding other people's opinions are also part of da'wa communication. The communication process carried out by preachers can become a benchmark for the success of Islamic communication and propagation. This article offers a new perspective on da’wa activities to increase interaction and develop communication in society. This concept is concerned with amthãl and tafsir as a learning method to increase public interest and interest in Islamic da’wa. Dialogue and communication of da'wa like this is what is popular with the community today as an effort to develop Islamic society. The data collection techniques in this study include field observation, interviews, and literature studies. The results of this study show that da'wa by using amthãl and tafsir as a learning method in the development of Islamic society in West Lombok can provide influence and change the community. This method of da’wa is classified as an innovative method of conveying and spreading the message of Islamic da’wa.